2011
DOI: 10.4300/jgme-d-10-00227.1
|View full text |Cite
|
Sign up to set email alerts
|

Educating Generalists: Factors of Resident Continuity Clinic Associated With Perceived Impact on Choosing a Generalist Career

Abstract: The continuity clinic experience 5 influence residents' GIM career choice. Residents who indicate they are more likely to pursue GIM based on that clinical experience have higher levels of satisfaction. Further prospective data are needed to assess if changes in continuity clinic toward these particular factors can enhance career choice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…Emphasizing outpatient training and education during residency while simultaneously providing protected time to practice ambulatory medicine may help retain resident interest in primary care. In addition to maximizing protected outpatient training time, there have been multiple appeals for a reform of the clinic experience itself 24,[30][31][32][33][34] as satisfaction with IM residency continuity clinic directly influences career choice toward primary care. 31,32 A recent study compared internal medicine residents' likelihood of entering GIM as a result of clinic to likelihood of entering a career in GIM before clinic, and demonstrated that 28 % were less likely to enter GIM as a result of their clinic experience, 59 % had no difference in likelihood, and only 11 % were more likely to enter general IM as a result of clinic.…”
Section: Discussionmentioning
confidence: 99%
“…Emphasizing outpatient training and education during residency while simultaneously providing protected time to practice ambulatory medicine may help retain resident interest in primary care. In addition to maximizing protected outpatient training time, there have been multiple appeals for a reform of the clinic experience itself 24,[30][31][32][33][34] as satisfaction with IM residency continuity clinic directly influences career choice toward primary care. 31,32 A recent study compared internal medicine residents' likelihood of entering GIM as a result of clinic to likelihood of entering a career in GIM before clinic, and demonstrated that 28 % were less likely to enter GIM as a result of their clinic experience, 59 % had no difference in likelihood, and only 11 % were more likely to enter general IM as a result of clinic.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are corroborated by a similar smaller study that found an association between workflow and professional/personal satisfaction and choice of GIM. 11 Collectively, these results demonstrate potential areas in which to focus efforts on improving the resident ambulatory clinic experience that may sway IM residents in the direction of primary care careers. Time management issues, such as the number of patients on their schedule, time allotted for patient care, and workflow issues, may adversely affect residents' perception of a future GIM career.…”
Section: Discussionmentioning
confidence: 99%
“…4 Many believe that dissatisfaction with the continuity clinic experience may discourage trainees from selecting primary care careers. [8][9][10][11] The challenges residents face during their continuity clinics include lack of continuity Published online April 18, 2013 with patients, burdensome administrative duties, lack of support for coordination of care and disease management, staffing shortages, distraction from inpatient duties, and dissatisfied primary care role models, all against the backdrop of managing patient panels full of medically and socially complex patients. [8][9][10][11] In an effort to improve the ambulatory continuity experience, several important stakeholders in IM have called for reform.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We included composite indices of learning opportunities (nine items), faculty teaching (10 items), and staff roles (eight items) by Roth et al [20]. We included two previously published items on likelihood of entering a general medicine career [21], one item on number of patients seen in a typical half-day session [22], and two items on satisfaction with the clinic [21,23] which used 5-point Likert scales ranging from ‘disagree strongly’ = 1 to ‘agree strongly’ = 5. The survey was pilot tested for face and content validity with five chief residents at one of the programs.…”
Section: Methodsmentioning
confidence: 99%